Utilization of Fan Palm, Date Palm, and Phragmites Australis fibers for improving the mechanical behavior of sandy soil. (March 2023) - Alhakim, Ghida; Jaber, Lina; Baalbaki, Oussama; Barraj, Firas
Abstract: Interests in the use of natural fibers as soil reinforcement are developing rapidly due to their cost effectiveness, high availability, and eco-friendliness. Many published studies investigated the advantages of fiber-reinforced soil, yet few of them used fibers extracted from Fan Palm (F.P), Date Palm (D.P) trees, and Phragmites Australis (Ph.A) stems, which are considered as by-products of these plants. Standard Proctor and Direct Shear tests were conducted with varying fiber contents of 0.5, 1, 1.5, and 2 %. It was demonstrated that the fiber inclusion increased the optimum moisture content, ductility, and dilation, while it decreased the maximum dry density and the brittleness of the soil. Moreover, the shear strength was significantly improved upon adding the fibers for all the contents and under the different normal stresses of 100, 200, 300, and 400 kPa. The optimum fiber percentages were found to be 2, 0.5, and 1 % for F.P, D.P, and Ph.A fibers, respectively, resulting in increasing the cohesion drastically by 10.6, 14.6, and 11.1 times the initial cohesion of the unreinforced soil, whereas, the angle of internal friction augmented by 11.9, 3.17 and 5.1 %. In summary, the application of the mentioned natural fibers improves the strength characteristics of the sand and is entirely in line with the principle of sustainable development and environmental conservation. Highlights: The incorporation of Fan Palm, Date Palm, and Phragmites Australis fibers presents challenges in sustainable soil improvement. An experimental study was performed to explore the effect of randomly distributed fibers on the soil shear behavior. The ductility of the sandy soil enhanced by using natural fibers. The dilative behavior of the granular material is influenced by the thickness of the fibers.